E-Module Development Using the Canva Application on Environmental Pollution Concept - Andika Wijaya Putra; Chairunnisah J. Lamangantjo; Ritin Uloli (Jurnal Penelitian Pendidikan IPA, 2024)
This research uses the ADDIE development model to produce an E-Module using the Canva application on environmental pollution concept that is Valid, Practical, and Effective. This research was conducted at SMP Negeri Molibagu involving students in Class VII. The research results show that the results of the validation of the E-Module using the Canva application from media experts achieved a score of 85%, which is included in the valid category and suitable for use in learning. The practicality of the E-Module using the Canva application as shown by the implementation of learning during three meetings with a percentage of 85% with excellent category, and the student responses reached 83% with excellent criteria. The effectiveness of the E-Module using the Canva application is demonstrated by student activity with a percentage of 86% with good criteria. Thus, it is concluded that the E-Module using the Canva application on environmental pollution concept has met the valid, practical, and effective criteria.